Optimasi Tingkat Layanan Call Center Jasa Teleponi Dasar: Kajian Regulasi - Hendro Purwadi (InComTech : Jurnal Telekomunikasi dan Komputer, 2019)
Service level in the call center is calculated based on the number of calls answered during the certain time intervals compared to the total number of calls received. The measurement of service level on the call center operator starts when the caller presses the menu to talk to the  operator on interactive voice response (IVR) menu, and is expressed as a percentage. The higher expected percentage of service level will be higher the needs of operator in the services.  Regulation in Indonesia determines service level for the call center of Basic Telephony Services is in the amount of more than or equal to 90% in 30 seconds. The author uses a business approach to the operational of the call center to analyze existing statutory data. Through the comparative method between operator occupancy and the costs required for the operation of call center using supply and demand curve, the optimum service level value at the call center of Basic Telephony Services can be known, which is 85% in 25 seconds. This means that 85% of incoming calls must be answered by the operator with a maximum waiting time of 25 seconds.